Pengaruh Pemanfaatan Teknologi Digital Terhadap Produktivitas Belajar Mahasiswa di Universitas Buana Perjuangan Karawang - Salsabila, Metha Aghshaina; Isyanto, Puji (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
The development of digital technology has brought major changes in various aspects of life, especially in the student learning process. This study aims to examine how much influence the use of digital technology has on the learning productivity of Buana Perjuangan University Karawang students. The method used is a quantitative approach with an associative research type. Data were collected through an online questionnaire distributed to 50 active students, then analyzed using validity, reliability, classical assumption tests, and simple linear regression. The results showed that all instruments used were declared valid and reliable. Based on the regression test results, which means there is a positive and significant influence between the utilization of digital technology on student learning productivity. This finding shows that the more optimal the utilization of digital technology in the learning process, the higher the student learning productivity, especially in terms of time effectiveness, task completion, and academic achievement.